A TEXTUAL ANALYSIS OF STUDENTS’ WRITING IN NARRATIVE TEXT - Laila Safitri; chairuddin chairuddin (Universitas 17 Agustus 1945 Semarang, 2021)
The objective of this study is to analyze cohesion and coherence in students’ narrative texts using critical discourse analysis approach and to identify the implications of applying critical discourse analysis approach to students’ narrative writing. This study used descriptive qualitative method. The object of this research is 6 narrative texts written by 2nd semester students of English Education Department of STKIP PGRI Bangkalan. Data collection is done through observation, questionnaires, interviews and documentation. The findings show that the students applied their narrative text writing tasks with grammatical cohesion, lexical cohesive, and coherence. Related to student assignment texts, most of them are good at writing cohesion and coherence and some of them need to be improved. In terms of writing, they are good at the reference, conjunction and reiteration or repetition. From student writings, the researcher got349 reference words collected, and 26 words from substitution, no ellipsis at all, 112 conjunction words collected, and the last 69 words lexical cohesive. They need to learn more about ellipsis and collocation, they are good at reiteration or repetition. About coherence they are good. most sentences are coherence but there is some to learn about coherence. Then, the implications of the critical discourse analysis approach model of Norman Fairclough are also very effective in analyzing a discourse or text because it can identify the content and intent of students’ narrative texts through three stages, namely the description stage, the interpretation stage and the explanation stage.